Disconnection from nature and interest in mass media. Issue 4 (1st October 2020) - Aruguete, Mara S.; Gillen, Meghan M.; McCutcheon, Lynn E.; Bernstein, Michael J.
Abstract: The main purpose of this study was to examine the association between interest in nature and attraction to the mass media. We measured environmental knowledge, environmental attitudes, and attraction to celebrities among a sample of 185 English-speaking community-based adults obtained through Mechanical Turk. A secondary purpose of the study was to validate measures of environmental attitudes and environmental knowledge. As predicted, those with greater attraction to celebrities showed less knowledge of the environment. Our results support the validity of the environmental attitude and environmental knowledge measures, although the two constructs appear to be only marginally related to one another. Implications for environmental education are discussed.